Theoretical and experimental study on the astigmatism self‐compensation in multi‐disk laser resonator based on exhaustive method. (25th October 2018) - Du, Jinyu; Yi, Jiayu; Yang, Zhongming; Yu, Yi; Tu, Bo; An, Xiangchao
Summary: In order to improve the quality of multi‐disk laser output beam quality, a theoretical method of astigmatism self‐compensation in multi‐disks resonator is developed based on which the maximization pre‐compensation of static aberration in the multi‐disk laser resonator is realized with the geometrical superposition of the astigmatism coefficient using the exhaustive method. In order to verify the theoretical method, a self‐compensating experiment has designed based on the theoretical method, which shows a clear improvement of the beam quality β .